2022
DOI: 10.1016/j.sleep.2021.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Circadian disturbances, sleep difficulties and the COVID-19 pandemic

Abstract: The COVID-19 pandemic has imposed extraordinary and unpredictable changes on our lifestyle for an unknown duration. Consequently, core aspects of wellbeing including behavior, emotion, cognition, and social interactions are negatively affected. Sleep and circadian rhythms, with an extensive impact on physiology, behavior, emotion, and cognition are inevitably affected too. We provided an updated overview of the impact of the COVID-19 pandemic on circadian rhythms and sleep based on the results of published stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 91 publications
(97 reference statements)
3
46
0
1
Order By: Relevance
“…These findings add to the existing literature on the mental health risk associated with non-male gender and financial pressure (25) (26) (27). They are also consistent with the view that circadian misalignment and sleep difficulties are common consequences of the pandemic that negatively affected core aspects of wellbeing and contributed to the aggravation of pre-existing psychological problems (28).…”
Section: Main Findingssupporting
confidence: 86%
See 1 more Smart Citation
“…These findings add to the existing literature on the mental health risk associated with non-male gender and financial pressure (25) (26) (27). They are also consistent with the view that circadian misalignment and sleep difficulties are common consequences of the pandemic that negatively affected core aspects of wellbeing and contributed to the aggravation of pre-existing psychological problems (28).…”
Section: Main Findingssupporting
confidence: 86%
“…Each question is weighted differently depending on the severity of the risk examined by the item: for example, the item asking participants 'how often have you failed to do what was normally expected of you because of your use of (first drug, second drug, etc)' is weighted more heavily than the question 'In the past three months, how often have you used the substances you mentioned (first drug, second drug, etc)?'. The average total score for all substances is used to evaluate risk: low risk (0-3), moderate risk (4-26) and high risk (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Substance Misusementioning
confidence: 99%
“…Social jetlag is a chronic misalignment between internal circadian clocks and external time (social time). Taken together, these results support the hypothesis that circadian misalignment could promote SARS-CoV-2 infection ( 6 , 7 , 8 ). Nevertheless, usual circadian misalignment as a risk factor for contracting Covid-19 has up to now been poorly studied.…”
Section: Introductionsupporting
confidence: 85%
“…While we found decreased cortical facilitation and lower neuroplasticity induction (same for both LTP and LTD) at the circadian nonpreferred time in that study (Salehinejad et al, 2021b), here we observed upscaled cortical excitability and a functionally different pattern of neuroplasticity alteration (i.e., diminished LTP-like plasticity induction and conversion of LTD-to LTP-like plasticity). Second, the results of the present study underscore the importance of sufficient sleep for adaptive and efficient performance (e.g., in working or educational environments) (Salehinejad et al, 2021a) which is specifically important in individuals with demanding jobs (e.g., night shift workers). Furthermore, the relevance of sleep for brain plasticity and optimal cortical excitability argues for the role of sufficient sleep in preventing disorders that are associated with cognitive and/or plasticity deficits, such as Alzheimer's disease (Ju et al, 2014) and major depression (Wolf et al, 2016) that constitute a growing public health concern.…”
Section: Discussionmentioning
confidence: 59%